Prioritization of Surgical, Obstetric, Trauma, and Anesthesia Care in South and Southeast Asian Countries’ Health Planning and Policy-making: 'SOTA Care Policies in South and Southeast Asia' - Saloni Mitra; Ritika Shetty; Shirish Rao; Sweta Dubey; Siddhesh Zadey (Annals of Global Health)
Background: Lack of policy prioritization of surgical, obstetric, trauma and anesthesia (SOTA) care in South and Southeast Asian countries could be a potential contributor to limited access to care. Objective: To assess the SOTA care prioritization in National Health Policies, Strategies, and Plans (NHPSPs). Methods: We analyzed NHPSPs from twelve South and Southeast Asian countries. These documents are considered the most important health-related policy statements. Bangladesh was excluded due to a lack of English translations. We searched sixteen electronic documents for a predefined list of keywords. The list included 52 keywords related to SOTA care and 7 keywords unrelated to SOTA care (used as a control). We used the keyword frequency (mentions per keyword or MPK) as a measure to compare prioritization between SOTA care and non-SOTA care. We further categorized the SOTA care keywords into five different Lancet Commission on Global Surgery (LCoGS) domains and eight subgroups. Findings: Across twelve NHPSPs, MPK value for SOTA care was 54.09 compared with 202.86 for non-SOTA, with eight NHPSPs having lower MPK values for SOTA care than non-SOTA keywords. Four NHPSPs had no mentions related to SOTA care financing and information management. Pediatric surgery and anesthesia were among the neglected subgroups. Conclusion: The analysis of South and Southeast Asian NHPSPs suggests that SOTA care issues are not prioritized in most countries. Pathways to greater policy attention include integrating SOTA care into ongoing health policy-making and planning efforts and developing and implementing specific national SOTA care plans.